Rabies: an evidence-based approach to management - L. Blumberg; J. Weyer; J. Frean; G.A. Ogunbanjo (South African Family Practice)
Human rabies in South Africa is largely due to infection with the classical rabies virus (genotype 1), with the yellow mongoose the commonest vector except in KwaZulu-Natal, Eastern Cape, Mpumalanga and now Limpopo provinces where the dog is predominantly responsible for most bites. Rabies is always fatal in humans but can be prevented by timeous administration of post exposure prophylaxis (PEP). This article discusses an evidence-based approach to rabies management in South Africa.